Parent Satisfaction With Outpatient Telemedicine Services During the COVID-19 Pandemic: A Repeated Cross-Sectional Study - Jones, Erin; Kurman, Jaime; Delia, Elisa; Crockett, Jennifer; Peterson, Rachel; Thames, Jasmin; Salorio, Cynthia; Kalb, Luther; Jacobson, Lisa; Stone, Jacqueline; Zabel, T. Andrew (Frontiers in Pediatrics, 2022)
Prior to the COVID-19 pandemic, the development of hospital-based telemedicine services had been slow and circumscribed in scope due to insurance and licensure restrictions. As these restrictions were eased during the COVID-19 pandemic to facilitate ongoing patient care, the public health emergency facilitated a rapid expansion and utilization of telemedicine services across the ambulatory service sector. Objectives: The current quality improvement (QI) study utilized this unprecedented opportunity to evaluate the use of telemedicine services across a variety of clinical disciplines and patient groups. Methods: Caregivers of patients (ages 0-21) who received care through an outpatient specialty center provided experience ratings of telemedicine services delivered during the initial pandemic months (March through June 2020; N=1,311) or during the national “winter surge” in late 2020 (November 2020 through February 2021; N=1,395). Questionnaires were distributed electronically following the clinical visits, and ANCOVA was employed (with patient age as the covariate) to determine if caregiver responses differed based on patient demographic characteristics. Results: Ratings of patient satisfaction with services were very strong at both time points; greater variability in scores was noted when caregivers were asked if they would use telemedicine services again. At both time points, younger patient age (i.e., age 0-5) was associated with decreased caregiver willingness to use telemedicine services in the future. Smaller effects were seen for certain “hands on” therapies (occupational, physical, speech) during the initial months of the pandemic and for proximity to the hospital during the “winter surge.” Conclusions: These data suggest a very positive overall caregiver response to telemedicine-based services during the COVID-19 pandemic. Several areas of potential improvement/innovation were identified, including the delivery of telemedicine therapies (e.g., occupational, physical, speech) services to young patients (i.e., age 0-5).